Analysis of the collected letters between Maruja Mallo and Alfonso Reyes - Pérez Rodríguez, Mª Antonia (Madrygal. Revista de Estudios Gallegos, 2013)
Analysis of the collected letters between Maruja Mallo and Alfonso Reyes (1938-1945), contextualizing them within the space-time framework in which they were written and within the relational and professional system between the painter (Maruja Mallo) and the writer (Alfonso Reyes). In this paper, these documents are compared with the correspondence they held with other intellectuals, and it takes into account how these letters contribute to get to know the evolution of their work, and the political and cultural activity of the people in exile. It is also analyzed the support of both to the Second Spanish Republic.